The Transformation From Leadership Behavior to Leadership Thinking (Journal of Education and Development, 2022)
Foreign research on teacher leadership has experienced three waves, from the personal behavior of teacher leaders to teaching ability and then to a position or a way of thinking. The behavior theory of teacher leadership mainly focuses on the formal position of teacher leaders, and sees the specific tasks of teacher leaders. The theory of teacher leadership mainly points to the classroom teaching leadership of teachers. Both see teacher leadership as an individual effort. On the other hand, the thinking mode of teacher leadership regards teacher leadership as a process of changing schools, a way and strategy to change organizational culture structure, and a collective effort. The research on teacher leadership has potential value for school improvement, which requires further clarifying the purpose of improving teacher leadership. The root of teacher leadership is to cultivate teachers’ sense of responsibility, promote the growth and development of teacher leadership from an appreciation perspective, and cultivate teachers’ appreciation eyes and appreciation ability.